Long-distance entanglement generation with scalable and robust two-dimensional quantum network - Li, Ying (2013)
We present a protocol for generating entanglement over long distances in a two-dimensional quantum network based on the surface-error-correction code. This protocol requires a fixed number of quantum memories at each node of the network and tolerates error rates of up to 1.67% in the quantum channels. If local operations are of an error rate of 10−3, error rates of about 1.27% in the quantum channels are tolerable.